A Brief Talk on Using Computer Aided Technology to Analyze the Feasibility of Introducing Ball Game in the Physical Education Courses of Applied Universities. Issue 3 (October 2020) - Luo, Wenfu
Abstract: On October 25, 2016, the Central Committee of the Communist Party of China and the State Council issued the "Outline for the "Healthy China 2030" Plan", which stated that the implementation of the Youth Sports Promotion Program, the cultivation of young people's sports hobbies, and the basic realization of adolescents' mastery of more than one sport. This paper uses computer-aided technology to conduct an empirical study on the influence of Dutch sports on the physical quality of college students through literature research, experimental methods and other research methods. The results show that: Ball sports can effectively improve the body's physical quality, especially the ability of women to run fast in short-term speed, aerobic work ability and ventilator function.